PENINGKATAN KOMPETENSI GURU MELALUI SUPERVISI AKADEMIK BERBASIS COACHING DENGAN PENDEKATAN INKUIRI KOLABORASI - Mohammad Yogi Hamdi; Ari Lutfia Sari; Putri Nabilah; Noviyanti; Theresa Heidi A Kanadjara; Lilis Suwandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of coaching-based academic supervision using a collaborative inquiry approach to enhance teacher competence at SMAN 23 Bandung. The research focuses on the execution of this supervision model, changes in teacher competence before and after its implementation, the approach's contribution to competence improvement, and the obstacles encountered along with strategies to overcome them. A qualitative descriptive research design was employed. Data were collected through observation, in-depth interviews, and document analysis, and subsequently analyzed using the stages of data reduction, data display, and conclusion drawing. The results indicate that coaching-based academic supervision utilizing a collaborative inquiry approach was carried out through stages involving planning, classroom observation, joint reflection, coaching, and follow-up in a participatory and collaborative manner. Implementing this approach successfully enhanced teacher competence across several areas: lesson planning, instructional delivery, the use of media and technology, learning evaluation, and self-reflection and professional development. Furthermore, the coaching approach encouraged teachers to become more reflective, creative, confident, and responsible for improving the quality of instruction. Obstacles identified included time constraints, uneven understanding of coaching among teachers, an underdeveloped culture of reflection, and the need for further improvement in principals' coaching skills. These challenges were addressed through improved supervision planning, ongoing dissemination and mentoring, the cultivation of a reflective habit, and training for supervisors. In conclusion, coaching-based academic supervision using a collaborative inquiry approach serves as an effective strategy for enhancing teacher competence while fostering higher-quality instruction and a collaborative culture within the school.